Ankylosaurus back sign: novel endoscopic finding in esophageal eosinophilia patients indicating proton pump inhibitor response - Ishimura, Norihisa (Endosc Int Open, 2018)
BACKGROUND AND STUDY AIMS : Characteristic endoscopic findings, such as linear furrows, rings, and whitish exudates, indicate the presence of esophageal eosinophilia (EE), though no specific findings are known to distinguish eosinophilic esophagitis (EoE) from proton pump inhibitor-responsive esophageal eosinophilia (PPI-REE). Here, we present a novel endoscopic finding in some EE patients possessing a linear longitudinal arrangement of whitish nodules with the appearance of the back of an Ankylosaurus dinosaur, termed Ankylosaurus back sign (ABS), and evaluations of its significance in affected patients. PATIENTS AND METHODS : Fifty-five patients diagnosed with EE (≥ 15 eosinophils/high power field) who were treated at our hospital and shown to evaluate a PPI response were enrolled. Endoscopic findings at baseline and clinical parameters were retrospectively reviewed. Furthermore, the clinicopathological features of patients with ABS, as well as the relationship between its presence and PPI response were evaluated. RESULTS:  Fifty-five patients (47 males, 8 females) with EE (17 with EoE, 38 with PPI-REE) were evaluated, of whom 50 (90.9 %) had linear furrows, the most frequently found feature, while ABS was found in 9 (16.4 %). Inter-observer agreement was substantial for ABS (κ 0.77). Interestingly, all patients with ABS had PPI-REE. Our findings revealed that the presence of ABS was closely associated with reflux esophagitis (RE) in patients with PPI-REE. CONCLUSIONS:  Although ABS was less frequent than typical endoscopic findings such as linear furrows in EE, this novel finding was closely associated with PPI-REE accompanied with RE. The clinical implications of ABS in patients with EE should be investigated further.